2002
DOI: 10.1002/art.10714
|View full text |Cite
|
Sign up to set email alerts
|

Cachexia in rheumatoid arthritis is not explained by decreased growth hormone secretion

Abstract: Objective. Patients with rheumatoid arthritis (RA) lose body cell mass (BCM) by unknown mechanisms. Since the loss of BCM in normal aging individuals parallels the characteristic age-related decline in growth hormone (GH) secretion, this study was carried out to determine whether further decreased GH secretion plays a role in the pathogenesis of this loss of BCM in RA patients, termed "rheumatoid cachexia."Methods. GH secretory kinetics were determined by deconvolution analysis in 16 patients with RA and 17 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 17 publications
3
22
1
1
Order By: Relevance
“…Since the primary objective of the present study was to compare the body fat content between RA patients and controls, the sample size was estimated by using the results of a previous study that investigated cachexia in RA (26). Based on the findings of body fat % in RA (40.5±10.3) and controls (36.0±8.2) in the study mentioned above, the sample size was calculated as 23 for both samples.…”
Section: Discussionmentioning
confidence: 99%
“…Since the primary objective of the present study was to compare the body fat content between RA patients and controls, the sample size was estimated by using the results of a previous study that investigated cachexia in RA (26). Based on the findings of body fat % in RA (40.5±10.3) and controls (36.0±8.2) in the study mentioned above, the sample size was calculated as 23 for both samples.…”
Section: Discussionmentioning
confidence: 99%
“…Accelerated muscle loss is observed at a higher age (sarcopenia), and in chronic diseases such as cancer and chronic obstructive pulmonary disease, and is collectively referred to as cachexia (20). In patients with RA, several studies, although not all, have shown evidence for a decreased FFM compared to healthy controls (21)(22)(23)(24)(25). In patients with AS, evidence is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The consequence is chronic erosion of BCM resulting in a cachectic state. Rheumatoid cachexia is associated with low bioavailability of insulin-like growth factor [13] but, differently from sarcopenia of aging, does not depend on reduced testosterone or growth hormone production [14].…”
Section: Body Composition In Rheumatoid Arthritismentioning
confidence: 98%